Neo-Zionism’s Vision for the Issue of the Jewishness of the State in Israel - Eloxory, Engy Waheed Fakhry (Dirasat: Human and Social Sciences, 2023)
Objectives: The purpose of the present paper is to analyze Neo-Zionism’s vision for the issue of the Jewishness of the state in Israel by tracing the foundations of this trend, the factors that helped crystalizing it in Israeli state, and the impact of that on the state’s identity. Methods: The paper is based on two approaches: the historical approach and the analytical approach, the first helps in tracing the intellectual roots of Neo-Zionism trend, while the second helps in dividing the phenomenon in question in order to identify its causes, analyze its vision’s results, and explain its impact on the identity of the Israeli state. Results: The Neo-Zionism trend presented a set of coherent values and ideas towards the issue of the Jewish state. In reality, Neo-Zionism was able to achieve the following: Firstly, the idolization of its visions. Secondly, the legitimization of its ideological visions. Thirdly, the legalization of its ideology and political approach. Although the trend presented a coherent intellectual perspective on the nature of the identity of the Israeli state, its religious vision led to a deepening of the identity crisis in Israeli society and created a new crisis between the nature of the identity of the state and the democratic system in Israel. Conclusions: the study recommends more research on the opposing visions to values and ideas of Neo-Zionism trend (left and Arab parties), and the alliances they can achieve in the face of the expansion of the Neo-Zionism.